Publication in Medical Education Scientific Area: A Challenging Journey in Disseminating Scientific Writing in Health Profession Education - Nurrokhmanti, Hikmawati; Arif, Luthfi Saiful; Sari, Silvia Mustika; Widyandana, Widyandana; Claramita, Mora (Universitas Gadjah Mada, 2024)
Background: Publications in the medical education field need more attention. It was shown by the MERSQI data score that there is no significant difference between medical education publications in the US (Society of General Internal Medicine, 44,4%) and Turkish (Turkish National Medical Education Congresses and Symposia, 11,3%) in 2014/2015. Therefore, specific strategies should be implemented to raise the quality and quantity of publications in the medical education area. With this recommendation, the number of publications in the medical education area is expected to increase.Gaps: In a study on the quality of publication in Turkish National Medical Education Congresses and Symposia, there is a significant difference in MERSQI score between unpublished (oral/poster presentation) and published papers.1 It is indicated that the quality of scientific papers needs to be increased. While in Indonesia, no further study is related to the quantity and quality of published papers. It is assumed that publication problems in the medical education field stem from the quality of scientific papers and could relate to Indonesian scholars' false publication strategy. Recommendation: The quality of scientific publications in Indonesia needs an improvement strategy that should be implemented in every scientific institution in Indonesia, starting from the master's degree level. The increasing proportion of research and any supporting material is expected to increase publication with high-quality research. The following recommendation is about the strategy of publishing the paper, which begins with selecting the fit or right scientific journal, followed by increasing scholar adherence to the journal's requirements.